2018
DOI: 10.1146/annurev-nutr-071816-064800
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21: A Versatile Regulator of Metabolic Homeostasis

Abstract: Fibroblast growth factor 21 (FGF21) is an endocrine hormone derived from the liver that exerts pleiotropic effects on the body to maintain overall metabolic homeostasis. During the past decade, there has been an enormous effort made to understand the physiological roles of FGF21 in regulating metabolism and to identify the mechanism for its potent pharmacological effects to reverse diabetes and obesity. Through both human and rodent studies, it is now evident that FGF21 levels are dynamically regulated by nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(155 citation statements)
references
References 155 publications
(321 reference statements)
4
151
0
Order By: Relevance
“…FGF21 is induced at the transcriptional level and released from murine liver in response to a remarkable diversity of nutritional stresses, including starvation, amino acid restriction, ketogenic and high-fat diets, simple sugars, and ethanol (BonDurant and Potthoff, 2018;. Among the transcription factors involved in FGF21 induction are PPARa, which induces FGF21 in response to starvation and ketogenic diet (Badman et al, 2007;Inagaki et al, 2007), and ChREBP, which induces FGF21 in response to simple sugars Iroz et al, 2017).…”
Section: Fgf21mentioning
confidence: 99%
“…FGF21 is induced at the transcriptional level and released from murine liver in response to a remarkable diversity of nutritional stresses, including starvation, amino acid restriction, ketogenic and high-fat diets, simple sugars, and ethanol (BonDurant and Potthoff, 2018;. Among the transcription factors involved in FGF21 induction are PPARa, which induces FGF21 in response to starvation and ketogenic diet (Badman et al, 2007;Inagaki et al, 2007), and ChREBP, which induces FGF21 in response to simple sugars Iroz et al, 2017).…”
Section: Fgf21mentioning
confidence: 99%
“…In recent years, several exclusively or predominantly liver-secreted proteins, termed hepatokines, have been identified as molecules possessing the capacity to exert potent metabolic effects, both locally and distally (Meex et al 2015). These include fibroblast growth factor 21 (FGF21), shown to modulate glucose and lipid metabolism (Kharitonenkov et al 2005, Potthoff et al 2009, Xu et al 2009, BonDurant and Potthoff 2018; follistatin, demonstrated to regulate muscle growth (Amthor et al 2004, Yaden et al 2014 and influence pancreatic beta cell function and survival (Zhao et al 2015, Hansen et al 2016a; and leukocyte cell-derived chemotaxin 2 (LECT2), which can promote both skeletal muscle and adipose tissue insulin resistance (Lan et al 2014, Jung et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblast growth factor 21 (FGF21), a regulator of energy metabolism, is mainly expressed and secreted by the liver, but other tissues, such as white and brown adipose tissue, skeletal muscle and cardiac muscle, also express and secrete FGF21 under certain circumstances in humans [1][2][3]. Whether FGF21 from these tissues contributes to circulating FGF21 concentrations and under what conditions is less clear [1]. Plasma concentrations of FGF21 are increased in human obesity.…”
Section: Introductionmentioning
confidence: 99%